Study of the dynamics of spindle shaft on gas-static bearings - Breshev, Oleksii; Nosko, Pavlo; Bashta, Oleksandr; Bashta (Sheremet), Alla; Radko, Maksym (My University, 2024)
This study delves into the complex dynamics of spindle shafts mounted on gas-static bearings, employing computational experiments and analysis to reveal crucial insights for optimizing high-precision machining processes

Це дослідження заглиблюється в складну динаміку шпиндельних валів, встановлених на газостатичних підшипниках, використовуючи обчислювальні експерименти та аналіз, щоб виявити важливі ідеї для оптимізації процесів високоточної обробки
Keywords: spindle dynamics; gas-static bearings; natural frequencies; computation; динаміка шпинделя; газостатичні підшипники; власні частоти; розрахунок; кафедра технології оздоровчих продуктів